Bad Break-Up Behavior: Break-Up Characteristics, Emotional Dysregulation, and Alcohol Use as Risk Factors for Cyber Dating Abuse Among Sexual Orientation Diverse College Students - Schroeder, Grace E. (Journal of interpersonal violence, 2024)
Cyber dating abuse (CDA) is a growing public health concern among college students. CDA includes monitoring and abusive behaviors perpetrated toward an ex-partner via technology. Little is known about the predictors of CDA, particularly among sexual minority (SM) college students. Some theorized but relatively untested predictors include break-up characteristics, emotional regulation deficits, and alcohol use. The current study investigates what factors are associated with an increased risk for CDA toward an ex-partner (i.e., break-up characteristics, emotional dysregulation, and alcohol use) and the differences in associations with CDA between heterosexual and SM college students. Participants (N = 661) self-reported their CDA perpetration following their worst romantic break-up. They also answered questions about the break-up, their emotional regulation skills, and their current alcohol use. While SM students (n = 191) reported greater emotion regulation difficulties and alcohol use, they did not significantly differ from heterosexual participants (n = 470) in their reported CDA perpetration post-break-up. Hierarchical regressions were conducted to determine the impact of break-up characteristics and individual factors on CDA perpetration. Break-up characteristics, emotional dysregulation, and alcohol use significantly predicted heterosexual participants’ CDA perpetration and accounted for 17% of the variance. Conversely, for SM students, only alcohol use was predictive of CDA, accounting for 5% of the variance. Although SM students report similar break-up experiences and levels of CDA as heterosexual students, additional, unmeasured factors may drive perpetration. However, given the generally high rates of alcohol use and CDA, and their robust association, interventions targeting alcohol reduction and healthy relationship dissolution strategies may be beneficial.